2016
DOI: 10.1891/1946-6560.7.1.55
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Dating Violence and Bystander Behavior: An Initial Investigation

Abstract: Preliminary research has demonstrated the utility of bystander interventions in reducing sexual assault (Coker et al., 2011; Moynihan & Banyard, 2008), and initial research has begun extending this type of intervention to dating violence broadly (i.e., physical and psychological aggression). However, there are many unexplored factors that may increase or decrease the likelihood that individuals will engage in bystander behavior. One such factor is previous experiences with dating violence and sexual assaul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
18
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 31 publications
3
18
1
Order By: Relevance
“…These data suggested that this was particularly true for women with a history of either physical or sexual victimization. Psychological victimization did not differentiate bystander intervention in this study (Woods et al, 2016). However, this research did not control for opportunity to intervene relative to reported intervention, nor did it examine differential intervention across situations (low risk, high risk, postassault), thus limiting its ability to detect differences in victimization status and gender as a function of the continuum of potential bystander intervention points.…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…These data suggested that this was particularly true for women with a history of either physical or sexual victimization. Psychological victimization did not differentiate bystander intervention in this study (Woods et al, 2016). However, this research did not control for opportunity to intervene relative to reported intervention, nor did it examine differential intervention across situations (low risk, high risk, postassault), thus limiting its ability to detect differences in victimization status and gender as a function of the continuum of potential bystander intervention points.…”
Section: Introductionmentioning
confidence: 84%
“…While the initial findings in this area are promising, most previous work views bystander intervention as a monolithic construct, and fails to account for (1) potential variance in opportunity, (2) risk that distinct circumstances present, and (3) previous personal experiences with violence (McMahon et al, 2015; Woods et al, 2016). Therefore, the current research addresses these limitations through examination of the contextual features of bystander intervention when individuals have the opportunity to intervene, and systematically examining the range of contexts in which individuals could intervene.…”
Section: Introductionmentioning
confidence: 99%
“…Because women face higher risk for sexual and physical violence victimization than men (Archer, 2000;Edwards et al, 2015), they may feel greater empathy toward others in similar risk situations (Burn, 2009;Woods et al, 2016) and thus be more willing to intervene as a bystander (Abbott & Cameron, 2014;Dovidio et al, 1991;Hortensius & de Gelder, 2018). Although Burn (2009) and Woods et al (2016) theorized that heightened bystander intervention tendencies among women reflect empathetic concerns, they did not include measures of empathy in these studies. In the present study, we examined the unique and additive effects of sexist attitudes and empathy in predicting bystander intervention and perceived barriers.…”
Section: Empathy and Bystander Interventionmentioning
confidence: 99%
“…Empathy is increased when individuals can identify with, or relate to, the person in need of help (Dovidio et al, 1991;Levine et al, 2005). Because women face higher risk for sexual and physical violence victimization than men (Archer, 2000;Edwards et al, 2015), they may feel greater empathy toward others in similar risk situations (Burn, 2009;Woods et al, 2016) and thus be more willing to intervene as a bystander (Abbott & Cameron, 2014;Dovidio et al, 1991;Hortensius & de Gelder, 2018). Although Burn (2009) and Woods et al (2016) theorized that heightened bystander intervention tendencies among women reflect empathetic concerns, they did not include measures of empathy in these studies.…”
Section: Empathy and Bystander Interventionmentioning
confidence: 99%
“…Total scores for each instance of victimization were calculated separately by adding the midpoint for each item response (e.g., a "4" for the response "3-5 times"), with higher scores representing more frequent victimization for each respective subscale. This project only utilized the sexual victimization subscale, and, consistent with previous research (Woods et al, 2016), utilized dichotomous categorization of victims, such that individuals who endorsed experiencing at least one act of violence were considered sexual victims. Example items from the sexual victimization subscale include "My partner made me have sex without a condom" and "My partner insisted on sex when I didn't want to".…”
Section: Methodsmentioning
confidence: 99%